Impact of Principal Communication and Psychological Climate on Enhancing Teacher Performance - Nurliana Nasution; Wahyuni Sri (AL-ISHLAH: Jurnal Pendidikan, 2025)
Effective school leadership relies heavily on communication, which plays a crucial role in shaping teacher performance. Additionally, a school’s psychological climate significantly influences teacher motivation, satisfaction, and professional engagement. While prior studies have explored these factors separately, limited research has examined their combined effect, particularly in the Indonesian context. This study investigates the joint impact of principals’ communication effectiveness and psychological climate on teacher performance in state high schools in Rumbai District, Pekanbaru City. Using a quantitative correlational design, data were collected from 93 teachers across three schools through Likert-scale questionnaires. Variables measured included principal communication effectiveness, psychological climate, and teacher performance. Data analysis employed descriptive statistics, t-tests, F-tests, and regression analysis. Results show that both principal communication (t = 16.631, p 0.001) and psychological climate (t = 4.171, p 0.001) significantly influence teacher performance. Together, these variables account for 86.2% of the variance in teacher performance (Adjusted R² = 0.862), indicating a strong predictive relationship. Descriptive findings also revealed moderate achievement levels (66%–73%) across all indicators. The study concludes that effective communication and a positive psychological climate are essential for fostering teacher engagement, performance, and a collaborative school culture. These findings highlight the strategic role of school principals as communicative leaders and underscore the need to prioritize communication and climate in leadership development programs.